STUDY OF INHIBITION IN HYDROTREATING CATALYTIC REACTION: THE EFFECT OF WATER - Fauzan Mushlihuddin, Muhammad
Crude oil is a complex material consisting of various types of hydrocarbons. Other content considered as an impurity is sulfur which can interfere petroleum refining processes and harm environment. Regulation to control sulfur content in diesel fuel in Indonesia has been issued through a Ministerial Regulation which requires the sulfur content in diesel to not exceed more than 50 ppm (Euro IV standard) and will be applied in 2021. Hydrotreating is a catalytic reaction carried out to remove impurity compounds in petroleum, including hydrodesulfurization reaction to remove sulfur. One of highly used catalysts in this reaction is NiMo/?-Al2O3. Catalyst performance in sulfur removal process can be impaired by the presence of inhibitor compound such as water. Inhibitor compounds can decrease the reaction rate kinetics thereby reducing the conversion of sulfur removal. This study aims to determine the kinetics model of HDS reaction for NiMo/?-Al2O3-P catalyst due to the influence of water. The examined catalyst is a PITD catalyst produced by the Chemical Reaction Engineering and Catalysis Laboratory, Chemical Engineering Department, Bandung Institute of Technology. HDS reaction was carried out at 50 bar operating pressure and temperature varies in range 290-340 °C with 150 ml of diesel feed and additional water of 300 ppm. The result showed that the water inhibitory effect on the HDS diesel reaction at the same pressure and temperature using a PITD catalyst caused the sulfur conversion to decrease. The longer the reaction is carried out, the more drastic the decrease in sulfur conversion occurs. At a reaction temperature of 340 °C, the sulfur conversion can decrease by 1,75 times lower than the sulfur conversion in the catalyst activity test without additional water. Water inhibition to the HDS diesel reaction also leads to a higher activation energy (Ea) value of about 1,086 the initial activation energy value, namely 81976 J/mol, while the value of the frequency factor (A) increases 2,2 times from the initial value of 4.9×106 hr-1.